Improving the Energy Efficiency of Kazakhstan’s Economy - ORYNKANOVA, Zhanar M.; BAIZHOLOVA, Raissa A.; ZEINULLINA, Aigul Zh. (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020, 2020)
This article discusses the main causes of the low energy efficiency and high energy intensity of Kazakhstan’s economy. A number of factors that constrain and enhance the process of improving the energy efficiency and energy saving of Kazakhstan’s economy are identified. The conducted studies substantiate the need to develop and adopt new measures in order to reduce the energy intensity of the country’s GDP. The analysis is based on statistics from the Committee on Statistics of the Ministry of National Economy of the Republic of Kazakhstan and the World Bank. The energy efficiency indicators of Kazakhstan’s economy are compared with those of the CIS and developed countries. This testifies to the objectivity of the findings. The article suggests measures to improve the energy efficiency of the country's economy, which are grouped by the nature of their impact into economic, social and organizational (administrative).